1977
DOI: 10.1111/j.1095-8649.1977.tb04095.x
|View full text |Cite
|
Sign up to set email alerts
|

Helminth and arthropod parasites of fishes in the mountain national parks of Canada

Abstract: Sixteen parasite species including one monogenean, two digeneans, five cestodes, six nematodes. one acanthocephalan, and one copepod were collected from 257 fish of 13 species examined from 32 lake and nine stream sites in the mountain National Parks of British Columbia and Alberta. The following parasites are reported from Alberta for the first time:

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

1983
1983
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 21 publications
0
4
0
Order By: Relevance
“… Sources: (1) Bangham & Adams (1954), (2) Mudry & Anderson (1977), (3) Szalai & Dick (1988), (4) Bangham (1955), (5) Muzzall (1984), (6) Wier et al. (1983), (7) Sandeman & Pippy (1967), (8) Kennedy et al.…”
Section: Methodsmentioning
confidence: 99%
“… Sources: (1) Bangham & Adams (1954), (2) Mudry & Anderson (1977), (3) Szalai & Dick (1988), (4) Bangham (1955), (5) Muzzall (1984), (6) Wier et al. (1983), (7) Sandeman & Pippy (1967), (8) Kennedy et al.…”
Section: Methodsmentioning
confidence: 99%
“…Moravec and Arai (1971) found that the rounded tail tip is another feature distinguishing it from other North American congeners. Rhabdochona cotti was reported from the slimy sculpin C. cognatus, the prickly sculpin C. asper Richardson, and the mottled sculpin C. bairdii Girard from different localities in Canada and the USA by Bangham and Adams (1954), Dechtiar (1972), Mudry and Anderson (1977), Arai and Mudry (1983), Muzzall and Sweet (1986), Heckmann et al (1987), and Muzzall and Whelan (1995). The present finding of R. cotti in C. caeruleomentum from Maryland represents a new host record and increases the known distribution of R. cotti in North America.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, in different countries, research has been conducted for a long time, not only for fish, but also for their parasites in Protected Areas. Some of the investigations concerned the parasite communities and species composition in different fish species (Mudry & Anderson, 1977;Boomker, 1994;Murcia et al, 2006;Morozińska-Gogol, 2007, 2009Butorina et al, 2008;Shukerova & Kirin, 2008;Moravec & Bakenhaster, 2010;Sandlund et al, 2010;Shukerova et al, 2010Shukerova et al, , 2017Sokolov & Gordeev, 2014;Chunchukova et al, 2016;Chunchukova & Kirin, 2018;Rubtsova & Kutsokon, 2018;Utevsky et al, 2018). Other studies devoted to different systematic groups include data on fish parasites in Protected Areas (Sasal et al, 2004;Galli et al, 2007;Kirjušina & Vismanis, 2007;Székely et al, 2009;Wood et al, 2013;Halajian et al, 2018;Hoogendoorn et al, 2020).…”
Section: Introductionmentioning
confidence: 99%